Respostas
respondido por:
4
r = a2 - a1
r = 15 - 3
r = 12
Temos a Razão desta P.A vamos encontrar an usando a fórmula do termo geral;
an = a1 + (n - 1)•r
a8 = 3 + (8 - 1)•12
a8 = 3 + 7•12
a8 = 87
Aplica-se a Fórmula da soma;
Sn = (a1 + an)•n/2
S8 = (3 + 87)•8/2
S8 = 90•8/2
S8 = 45•8
S8 = 360
r = 15 - 3
r = 12
Temos a Razão desta P.A vamos encontrar an usando a fórmula do termo geral;
an = a1 + (n - 1)•r
a8 = 3 + (8 - 1)•12
a8 = 3 + 7•12
a8 = 87
Aplica-se a Fórmula da soma;
Sn = (a1 + an)•n/2
S8 = (3 + 87)•8/2
S8 = 90•8/2
S8 = 45•8
S8 = 360
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás